2015
DOI: 10.1038/leu.2015.134
|View full text |Cite
|
Sign up to set email alerts
|

IKZF1 deletion is an independent prognostic marker in childhood B-cell precursor acute lymphoblastic leukemia, and distinguishes patients benefiting from pulses during maintenance therapy: results of the EORTC Children's Leukemia Group study 58951

Abstract: The added value of IKZF1 gene deletion (IKZF1(del)) as a stratifying criterion in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is still debated. We performed a comprehensive analysis of the impact of IKZF1(del) in a large cohort of children (n=1223) with BCR-ABL1-negative BCP-ALL treated in the EORTC-CLG trial 58951. Patients with IKZF1(del) had a lower 8-year event-free survival (EFS, 67.7% versus 86.5%; hazard ratio (HR)=2.41; 95% confidence interval (CI)=1.75-3.32; P<0.001). Importantly, despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
96
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 29 publications
8
96
1
3
Order By: Relevance
“…Deletions in the IKZF1 gene encoding the B-cell transcription factor IKAROS have been linked to an unfavorable clinical outcome of BCP-ALL in different treatment protocols, including recent protocols with risk stratification guided by minimal residual disease monitoring. [3][4][5][6][7][8][9][10][11] The IKZF1 gene located on chromosome band 7p12.2 consists of 8 exons. Exons 2 to 8 contain the protein-coding sequence of IKAROS (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Deletions in the IKZF1 gene encoding the B-cell transcription factor IKAROS have been linked to an unfavorable clinical outcome of BCP-ALL in different treatment protocols, including recent protocols with risk stratification guided by minimal residual disease monitoring. [3][4][5][6][7][8][9][10][11] The IKZF1 gene located on chromosome band 7p12.2 consists of 8 exons. Exons 2 to 8 contain the protein-coding sequence of IKAROS (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…16, 17, 18 Irrespective of the type of IKZF1 alteration, they prevail in poor responding cases in major treatment protocols. 5, 11, 17, 19, 20, 21, 22, 23 They are a hallmark of high-risk BCP ALL, especially those, which carry a BCR-ABL1 and other cytokine- and kinase-activating fusions, including IGH-CRLF2 and P2RY8-CRLF2. 11, 24 The common characteristic of such cases is a gene expression signature that resembles that of genuine BCR-ABL1 -positive cases and which are, therefore, also referred to as either ' BCR-ABL1 -like' or 'Ph-like'.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent studies have shown: (1) deletions or mutations of IKZF1 gene correlate with poor prognosis in other subtypes of pre-B ALL, thus providing evidence that IKAROS protein is an important tumor suppressor in pre-B ALL, (2) IKZF1 alterations have been reported in pre-B ALL carrying BCR-ABL1 rearrangement and have been associated with poor treatment outcome, (3) occurrence of IKZF1 aberrations in association with other genetic alterations such as JAK mutations and translocations involving chemokine receptor like factor 2 (CRLF2) in childhood ALL, and (4) IKZF1 alterations in B-cell ALL lead to induction of multiple genes associated with proliferation and treatment resistance suggesting identification of new therapeutic targets for HR disease [101,105,107]. Recently, there have been controversial reports on the benefit of intensifying conventional maintenance chemotherapy by giving vincristine and glucocorticoid pulse therapies in patients with IKZF1 deleted ALL [111,112].…”
Section: Birinapantmentioning
confidence: 99%